Identifying genomic surveillance gaps in Africa for the global public health response to West Nile virus: a systematic review - Moir, M.; Sitharam, N.; Hofstra, L.M.; Dor, G.; Mwanyika, G.; Ramphal, Y.; Reichmuth, M.L.; San, J.E.; Gifford, R.; Wilkinson, E.; Tshiabuila, D.; Preiser, W.; et al. (Elsevier, 2025)
West Nile virus (WNV) is a priority pathogen that poses a high risk for public health emergencies of global concern. Although WNV is endemic to Africa, only few (n=63) whole genomic sequences are available from the continent. In this Review, we examined the status of the molecular testing and genomic sequencing of WNV across Africa and mapped its global spatiotemporal spread. WNV has been detected in 39 African countries, the Canary Islands, and Réunion Island. Although publications, including those with molecular data, originated from 24 of these countries, genomic sequences were available from only 16 countries. Our analysis identified regions with detected viral circulation but without molecular surveillance. The current literature has substantial knowledge gaps in terms of the disease burden, molecular epidemiology, and distribution of WNV in Africa. Addressing these gaps requires an integrated One Health surveillance approach, which is challenging to establish. We propose three key surveillance needs that could improve the current understanding of the WNV disease burden in Africa, to strengthen the global public health response to this vector-borne disease.